Peningkatan Keterampilan Membaca dan Menulis Permulaan dengan Menggunakan Model Inkaber Bagi Siswa Kelas 1 SDN 101280 Gunung Tua Tonga Tahun Ajaran 2024/2025 - Melati Aderina; Faisal Faisal; Elvi Mailani; Halimatussakdiah; Apiek Gandamana (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to improve the early reading and writing skills of first-grade students at SDN 101280 Gunung Tua Tonga in the 2024/2025 academic year through the implementation of the Inkaber model (Inductive Picture-Word Model). The background of this research is based on the low early literacy skills of students, indicated by an average score of 1.39 on a 1–4 scale, as well as the minimal use of media and engaging learning approaches. This research is a Classroom Action Research (CAR) using the Kemmis & McTaggart model, conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The objectives of this study are to describe the initial conditions of students' reading and writing skills, to portray the learning process using the Inkaber model, and to explain the improvement in literacy performance after the implementation. The results showed that the application of the Inkaber model significantly improved students’ reading and writing skills. In the initial condition, the average writing score was 58.5 and the reading score was 60.2, with most students not meeting the Minimum Competency Criteria (MCC). After two cycles of implementation, all students met the MCC with an average writing score of 85.24 and reading score of 84.70. The conclusion of this study is that the Inkaber model is effective for use in early literacy learning. The combination of visual media, interactive approaches, and contextual learning strategies made the lessons more engaging and meaningful for lower-grade students. This model is recommended as an alternative for improving early reading and writing skills in elementary schools.